Select Resources for Image-based Humanities Computing. - Nowviskie, Bethany (Computers & the Humanities, 2002)
The article presents a list of papers and books related to the image-based humanities computing. Some of the books enlisted are "Creating and Distributing High Resolution Cartographic Images," by David Yehling Allan, "Languages of Visuality: Crossings Between Science, Art, Politics, and Literature," edited by Beate Allert, "Introduction to 3-D Spatial Visualization," by , Beverly Baartmans, "IEEE Conference on Information Visualization: An International Conference on Computer Visualization and Graphics," by Ebad Banissi, Farzad Khosrowshahi, and Muhammad Sarfraz and others.